Crypto-Governance: The Ethical Implications of Blockchain in Public Service. (2nd January 2022) - Heckler, Nuri; Kim, Yeonkyung
Abstract : Blockchain systems are positioned to revolutionize many aspects of governance and public service. This paper explores the ethical implications of blockchain for government ethics leaders implementing and managing blockchain systems. Blockchain is a unique challenge and opportunity for democratic governance because of its transparency, security, efficiency, and decentralization. In particular, blockchain could significantly change public entities ethical relationship to citizen privacy, social equity, and administrative evil.